2009
DOI: 10.4319/lom.2009.7.42
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phosphorus, calcium, iron, and other elements in organisms at sub‐micron resolution using X‐ray fluorescence spectromicroscopy

Abstract: X-ray spectromicroscopy (combined X-ray spectroscopy and microscopy) is uniquely capable of determining sub-micron scale elemental content and chemical speciation in minimally-prepared particulate samples. The high spatial resolutions achievable with this technique have enabled the close examination of important microscale processes relevant to the cycling of biogeochemically important elements. Here, we demonstrate the value of X-ray microscopy to environmental and biological research by examining the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Further analysis of algal cells has shown that polyphosphate can be associated with Ca and iron in organic matter (Diaz et al, 2009) and that polyphosphate in diatoms may be converted to authigenic apatite in coastal sediments . At low sediment concentra tions of P, distinguishing between the various phases can thus be difficult.…”
Section: Removal Of Phosphorus From Estuaries and The Coastal Oceanmentioning
confidence: 99%
“…Further analysis of algal cells has shown that polyphosphate can be associated with Ca and iron in organic matter (Diaz et al, 2009) and that polyphosphate in diatoms may be converted to authigenic apatite in coastal sediments . At low sediment concentra tions of P, distinguishing between the various phases can thus be difficult.…”
Section: Removal Of Phosphorus From Estuaries and The Coastal Oceanmentioning
confidence: 99%
“…New analytical technologies are greatly advancing our understanding of the biotic and abiotic processes controlling P‐cycling at the molecular‐ to microscale, such as synchrotron X‐ray fluorescence spectromicroscopy (Diaz et al, 2009) and P‐31 nuclear magnetic resonance spectroscopy (Cade‐Menun et al, 2006). New in situ monitoring techniques for measuring sediment–water P fluxes such as diffusive equilibrium in thin film technology (Jarvie et al, 2008; Palmer‐Felgate et al, 2010), high‐resolution bankside water P analyzers (Jordan et al, 2007; Palmer‐Felgate et al, 2008), and detailed in‐stream nutrient spiraling and process studies (Demars, 2008; Stutter and Lumsdon, 2008) are providing greater detail on mechanisms of P flux regulation at the river reach scale.…”
mentioning
confidence: 99%
“…10 In addition, SR-XRF is capable of elemental distribution mapping within individual cells at a resolution of 0.2-0.3 µm and has successfully been used to study the uptake of metals in mammalian cells. [12][13][14][15] Studies by Twinning and coauthors 16,17 and Diaz 18 also showed that microprobe SR-XRF was useful in determining the elemental composition and distribution of elements (Si, P, S, K, Ca, Mn, Fe, Co, Ni, Cu and Zn) in a range of marine microalgae isolated from oceanic waters and in two freshwater algae in laboratory culture media, respectively. This study uses correlative microprobe SR-XRF and XANES to investigate the internalisation of Cu in Cu-exposed marine microalgal cells to determine the toxicological modes of action of the metal.…”
Section: Introductionmentioning
confidence: 99%